Patterns of regional recurrence in papillary thyroid cancer patients with lateral neck metastases undergoing neck dissection - Jason J. Xu; Eugene Yu; Caitlin McMullen; Jesse Pasternak; Jim Brierley; Richard Tsang; Han Zhang; Antoine Eskander; Lorne Rotstein; Anna M. Sawka; Ralph Gilbert; Jonathan Irish; et al. (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Practice variability exists for the extent of neck dissection undertaken for papillary thyroid carcinoma (PTC) metastatic to the lateral neck nodes, with disagreement over routine level V dissection. Methods We performed a retrospective medical record review of PTC patients with lateral neck nodal metastases treated at University Health Network from 2000 to 2012. Predictive factors for regional neck recurrence, including extent of initial neck dissection, were analyzed using Cox regression. Results Out of 204 neck dissections in 178 patients, 110 (54%) underwent selective and 94 (46%) had comprehensive dissection including level Vb. Mean follow-up was 6.3 years (SD). Significant predictors of regional failure were the total number of suspicious nodes on preoperative imaging (p = 0.029), largest positive node on initial neck dissection (p < 0.01), and whether patients received adjuvant radiotherapy (p = 0.028). The 5-year ipsilateral regional recurrence rate was 8 and 9% with selective and comprehensive dissection, respectively (p = 0.89). Conclusion The extent of neck dissection did not predict the probability of regional recurrence in PTC patients presenting with lateral neck metastases.